Evaluation of p-GaN-gate All-GaN Cascode HEMT on SiC Substrate: DC Characteristics and Switching Performance - Dian-Ying Wu; Chih-Yung Hsieh; Yi-Xian Huang; Yu-Chen Liu; Wen-Ching Hsu; Ci-Ze Li; Jia-Zhe Liu; Cheng-Yeu Wu; Meng-Chyi Wu (IEEE Journal of the Electron Devices Society)
This article compares p-GaN-gate all-GaN cascode devices with standalone E-mode HEMTs on SiC substrates, with a focus on double pulse testing (DPT), a critical method for evaluating switching performance under realistic operating conditions. The all-GaN cascode, featuring a gate width of 85 mm, demonstrates a current rating of 15.6 A, an on-resistance of 7.7 m $Ω $ -cm2, a breakdown voltage of 970 V, and turn-on/off times of 71/52 ns, respectively. Additionally, it exhibits switching energy losses of 17/ $8.2~μ $ J at $V_{DS} \,\, {=} \,\, 400$ V and $I_{DS} \,\, {=} \,\, 1$ A. Its dynamic RDS,on is measured at $0.7~Ω $ at $V_{DS} \,\, {=} \,\, 300$ V and $I_{DS} \,\, {=} \,\, 1$ A. The experimental results indicate a significant improvement compared to the standalone E-mode HEMT. This highlights the advantages of the all-GaN cascode in reducing dynamic resistance and enhancing switching efficiency, making it an excellent choice for high-performance applications.